Wayang Kulit Sebagai Representasi Kehidupan Sosial dalam Karya Seni Lukis Kontemporer - Rahmad Al Mutaqqim; Yasrul Sami (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Wayang kulit is a traditional art form that embodies moral, social, and spiritual values, while representing human life. In today’s social context, marked by challenges such as power manipulation, economic inequality, and the decline of moral values, wayang kulit remains relevant as a medium of reflection and social critique. This artistic creation applies Bandem’s consortium art method with five stages: preparation, elaboration, synthesis, concept realization, and completion. Through contemporary painting, wayang kulit characters are reinterpreted in expressive and symbolic visual styles. The artwork serves not only as an artistic expression but also as a cultural preservation effort that bridges traditional values with contemporary realities. It is expected that this work will strengthen cultural awareness, function as a medium of social critique, and open broader opportunities for artistic exploration